O gênero capa de revista: a forma que constrói sentidos na e pela linguagem - Asturian, Alan (2016)
This work, entitled The genre magazine cover: the form that builds meanings in and through the language, aims to analyze four covers of Veja Magazine, published days before the final votes of Brazilian presidential elections of 2002, 2006, 2010 and 2014, from the prism of the enunciative theory by Benveniste to emphasize that the language is the only system of signs able to interpreting itself and the others systems. Furthermore, we try to describe the media how opinion maker, through the magazine covers; identify in the analyses the modes of significance – semiotic and semantic; build an enunciative analysis of the corpus. A study of this kind justified by the need to understand the capacity of the language to build senses, as well as the power of media to inform and form the public through the agenda-settings. To realize the analyses of this master’s thesis, classified as a descriptive, bibliography and qualitative research, we will use the benvenistian perspective of enunciation, particularly in the texts Subjectivity in language (1958) that presents person's categories, I and you, and the non-person he; Language and human experience (1965) that builds the notions of physical, chronic and linguistic time; Form and Meaning in Language (1966) that establishes the twin notions of form and meaning, semiotic mode (mean) and semantic mode (communicate) and Semiology of Language (1969) that highlights the language between the sign systems because it possesses a double nature that gives it the ability to interpret the other systems and itself. The covers will be contextualized, after we will describe the visual and verbal elements, to then analyze the enunciative scene composed by the categories of person, time and place. Finally, we emphasize that this work supplies subsides to promote a reader more critical face to the constants information transmitted by the media, as well to highline the fundamental function of language inherent to the human essence.